ESTIMATION OF HETEROSIS FOR SEED YIELD AND OIL CONTENT IN SUNFLOWER HYBRIDS (Helianthus annuus L.) - S. NEELIMA, K. VARALAKSHMI and (The Journal of Research, PJTSAU, 2020)
The experimental material consists of four cytoplasmic male sterile lines and six testers crossed in a line x tester fashion to develop 24 sunflower hybrids during kharif, 2017 at Regional Agricultural Research Station, Nandyal. The hybrids and parents along with three checks (NDSH-1012, DRSH-1 and KBSH-44) were evaluated for ten traits during rabi, 2018 - 19. The results showed existence of high significant differences among genotypes for all the traits. The extent of heterosis in 24 hybrids over midparent (MP) ranged from 16.10 to 216.58 percent and over better parent (BP) from -1.05 to 133.81 for seed yield and the standard heterosis indicated that the cross NDLA-4 x NGM-16 exhibited significantly high positive heterosis over DRSH-1 (42.86) and KBSH-44 (65.14) and also the same cross noted to have high positive standard heterosis for NDSH-1012 (24.13). While the extent of heterosis for oil content over mid parent (MP) and better parent (BP) ranged from -0.70 to 18.32 and -5.23 to 9.77 respectively, and regarding the standard heterosis, the cross CMS-30 A x NO-30 expressed significantly high positive heterosisover the standard checks DRSH-1 (5.37) and KBSH-44 (17.45). The best crosses viz., NDLA-4 x NGM-16, CMS-17 A x NO-15 and CMS-17 A x NGM-16 were identified as promising for seed yield and its contributing traits based on their heterosis over better parent, gca, sca effects and per se performance and these better performing hybrids can be used for exploiting hybrid vigour in future breeding programmes.